2004
DOI: 10.1139/t04-019
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance effects in pressuremeter tests in clay

Abstract: This paper analyzes the effect of borehole disturbance, caused by installation of pressuremeter probes in clays, on the derived stress-strain curves. Both overpushing-and overcutting-induced disturbances are considered. It is shown that overpushing results in underestimation of the undrained shear resistance. In general, the degree of underestimation cannot be determined. As for overcutting, the derived stress-strain curves are characterized by high peak strengths. The degree of overestimation of the undrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The stress strain behavior of the cohesive soil is assumed to follow either a linear elasticity relation (Gibson and Anderson (1961) and Silvestri ( 2003)) a hyperbolic elastoplastic relation (Silvestri (2004)) or a power law (Bolton and Whittle (1999)).…”
Section: Conventional Limit Pressurementioning
confidence: 99%
“…The stress strain behavior of the cohesive soil is assumed to follow either a linear elasticity relation (Gibson and Anderson (1961) and Silvestri ( 2003)) a hyperbolic elastoplastic relation (Silvestri (2004)) or a power law (Bolton and Whittle (1999)).…”
Section: Conventional Limit Pressurementioning
confidence: 99%
“…The two-dimensional axisymmetric idealised geometry of the self-boring pressuremeter was constructed with approximately 110 15-node triangular elements in order to avoid mesh-dependent results [56]. To avoid the influence of the external boundaries, the geometry was extended 30 times the initial cavity radius a 0 [21,53,62]. Simulation took place assuming fully undrained conditions.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…The SBP was also conceived as an instrument that will cause minimal disturbance in the soil during installation [4,6,11]. However, later research has shown that the insertion of a SBP into the ground is not always perfect [2,17,33,35,46,53]. Installation defects such as overdrilling, underdrilling and partial pushing may all take place as the instrument is advanced into the soil.…”
Section: Introductionmentioning
confidence: 99%